THE PERFORMANCE OF PREDICTIVE INDEX FOR OSTEOPOROSIS (PIO) AND OSTEOPOROSIS SELF-ASSESSMENT TOOL FOR ASIANS (OSTA) AS A CLINICAL TOOL FOR IDENTIFYING THE RISK OF OSTEOPOROSIS IN ADULTS - Gadong, Lyza Camille; Cabral, Monica Therese; Capellan, Maria Leonora; Ang-Golangco, Nerissa (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION A new clinical tool, the Predictive Index for Osteoporosis in Men (PIO) which includes current smoking status has been recently developed to identify the risk of osteoporosis in men under 70 years old7 . OBJECTIVES To compare the performance of Predictive Index for Osteoporosis (PIO) with Osteoporosis Self-Assessment Tool for Asians (OSTA) as a clinical tool for identifying the risk of osteoporosis in Filipino men 50–69 years of age and Filipino women 50–65 years of age. METHODOLOGY This was an analytic study that employed a cross sectional approach that included Filipino men and women seen at the Outpatient Charity Department or at the private clinics and who underwent DXA. All the subjects completed a structured questionnaire and their weight and height were obtained, from which their PIO and OSTA scores were computed. RESULTS A total of 81 patients were included in the study. Patients diagnosed with osteoporosis on DXA was found to have a lower BMI at less than 21. OSTA has an area under the curve of 0.712 which turns out to be significant (p=.0004), with a calculated likelihood ratio of 1.64. The ROC of PIO showed that the optimal cut off is >0.962 and the calculated likelihood ratio that this patient may have osteoporosis is 1.38. Comparing the sensitivity and specificity, the resulting p value of 0.2728 denotes that the AUC curve of the two tools is not significantly different. CONCLUSION PIO has similar sensitivity and specificity to OSTA in predicting the risk for osteoporosis in Filipino men and women.